Stages of Development of Phraseology of the Uzbek Language (Texas Journal of Philology, Culture and History, 2023)
This article discusses the stages of development of the phraseology of the Uzbek language, and also presents a small analysis of the phraseological units of the Uzbek language. This is the soul of any national language, in which the spirit and originality of the nation is expressed in a unique way. Phraseology, being part of the language picture of the world, reflects the national mentality of a native speaker